Improving Performance in Mixture Porous Asphalt: Application Polyethylene-Terephthalate (PET) and Lawele Granular Asphalt (LGA): Peningkatan Kinerja pada Campuran Aspal Berpori: Aplikasi Polyethylene-Terephthalate (PET) dan Lawele Granular Asphalt (LGA) - Oktaviastuti, Blima; Sadillah, Muhammad; Primaswo, Rifky Aldila (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2023)
Plastic has various types, one of which is PET (Polyethylene Terephthalate) plastic, which is often used as a raw material for plastic bottles. One type of asbuton that is often used for road pavement is LGA (Lawele Granular Asphalt) asphalt. Repairs by adding asbuton to the porous asphalt mixture need to be done. This is because porous asphalt has several weaknesses, namely low strength or stability compared to other asphalt mixtures. The addition of PET and LGA waste to porous asphalt is a topic in this article. This research design uses a quantitative design with a type of experimental research. The results of the study concluded that: (1) The results of testing the characteristics of the constituent ingredients of the porous asphalt mixture meet the specifications of SNI, and (2) The test results of the addition of PET (Polyethylene Terephthalate) plastic and LGA (Lawele Granular Asphalt) to porous asphalt mixture meet the specifications by RSNI 2 Design and Implementation of Porous Asphalt Mixture 2012. It is hoped that this research can be an alternative to the mixture of PET plastic waste and LGA asbuton in a porous asphalt mixture. In addition, the newness of this material is expected to also help the construction of roads.